Direct comparison of whole heart quantifications between different retrospective and prospective gated 4D flow CMR acquisitions - Fischer, Kady; Grob, Leonard; Setz, Louis; Jung, Bernd; Neuenschwander, Mario D.; Utz, Christoph D.; von Tengg-Kobligk, Hendrik; Huber, Adrian T.; Friess, Jan O.; Guensch, Dominik P. (Frontiers in Cardiovascular Medicine, 2024)
Introduction 4D flow cardiovascular magnetic resonance (CMR) is a versatile technique to non-invasively assess cardiovascular hemodynamics. With developing technology, choice in sequences and acquisition parameters is expanding and it is important to assess if data acquired with these different variants can be directly compared, especially when combining datasets within research studies. For example, sequences may allow a choice in gating techniques or be limited to one method, yet there is not a direct comparison investigating how gating selection impacts quantifications of the great vessels, semilunar and atrioventricular valves and ventricles. Thus, this study investigated if quantifications across the heart from contemporary 4D flow sequences are comparable between two commonly used 4D flow sequences reliant on different ECG gating techniques. Methods Forty participants (33 healthy controls, seven patients with coronary artery disease and abnormal diastolic function) were prospectively recruited into a single-centre observational study to undergo a 3T-CMR exam. Two acquisitions, a k-t GRAPPA 4D flow with prospective gating (4Dprosp) and a modern compressed sensing 4D flow with retrospective gating (4Dretro), were acquired in each participant. Images were analyzed for volumes, flow rates and velocities in the vessels and four valves, and for biventricular kinetic energy and flow components. Data was compared for group differences with paired t-tests and for agreement with Bland-Altman and intraclass correlation (ICC). Results Measurements primarily occurring during systole of the great vessels, semilunar valves and both left and right ventricles did not differ between acquisition types (p > 0.05 from t-test) and yielded good to excellent agreement (ICC: 0.75–0.99). Similar findings were observed for the majority of parameters dependent on early diastole. However, measurements occurring in late diastole or those reliant on the entire-cardiac cycle such as flow component volumes along with diastolic kinetic energy values were not similar between 4Dprosp and 4Dretro acquisitions resulting in poor agreement (ICC < 0.50). Discussion Direct comparison of measurements between two different 4D flow acquisitions reliant on different gating methods demonstrated systolic and early diastolic markers across the heart should be compatible when comparing these two 4D flow sequences. On the other hand, late diastolic and intraventricular parameters should be compared with caution.